Enteritis necroticans and Clostridium perfringens type C; Epidemiological and pathological findings over the past 20 years. - Stuart Johnson; Andrew M Skinner; Calob Lostutter; Trevor Duke; Horst Posthaus (PLoS Neglected Tropical Diseases)
Enteritis necroticans (EN) in humans caused by infection with Clostridium perfringens type C, once thought limited to the highlands of Papua New Guinea has been identified sporadically worldwide. Outbreaks still occur among children in low-income countries and isolated cases occur among children and adults in other countries. Here the disease seems to be associated with diabetes mellitus and other risk factors. C. perfringens type C is also an important cause of necrotizing enteritis among animals, particularly pigs. Research into the pathogenesis of this disease has confirmed the central role of beta toxin and its target, the endothelial cell. Unlike most bacterial enteric infections, the primary anatomic location of EN is the proximal small intestine, reasons for which are not completely understood. Ongoing surveillance for C. perfringens type C infection is warranted as well as public health measures of prevention in locations where environmental and food hygiene is poor.